Effects of teacher leadership on parent-teacher collaboration at the elementary school in Nanjing, China. - Quanjin, Rong; Hassan, Aminuddin Bin; Omar, Muhd Khaizer (Human Resources Management Academic Research Society (HRMARS), 2024)
Teacher's role in fostering effective parent-teacher collaboration is critical for the educational process and can greatly influence its growth. This study investigates how primary school teacher leadership influences parent-teacher cooperation in Nanjing, Jiangsu Province. This article utilises the five forces model of leadership and incorporates teachers' professional traits to provide an analytical framework for teacher leadership, aiming to provide a thorough examination of the current state of teacher leadership. An analytical approach is developed to evaluate the existing state of parent-teacher collaboration simultaneously. This approach utilises existing literature and collaboration theory to provide a thorough grasp of the status of parent-teacher collaboration. The parent data was analysed using descriptive statistical analysis and Pearson correlation. This dual method enables a thorough investigation into the impact of teacher leadership on parent-teacher collaboration. The study revealed that the general state of parent-teacher collaboration is positive, with notable variations among parents in their level of cooperation. Teacher leadership plays a crucial role in fostering parent-teacher cooperation, and its various sources of influence have distinct effects across different dimensions. If the research results are applied to real-life scenarios, then teachers will assume a more influential leadership position, thereby helping parents to become more involved in parent-teacher collaboration, increasing the overall effectiveness of the collaboration, and ultimately promoting the development of elementary school students in Nanjing, Jiangsu Province.